Shawllira On The Go Application - Shahrel Anuar, Danial Azwar; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2022)
Shawllira On The Go application is an e-commerce application based on Android platform and a web based system developed specifically for the Shawllira Sdn. Bhd. The Android based applications are developed specifically for Shawllira customers while Shawllira administrators use the web-based system. The system aims to solve the problem of irregular business data storage, non-parallel sales record keeping and the problem of customers to purchase products from Shawllira. With this system, Shawllira can store their business data such as product stock data and sales record data more systematically. In addition, Shawllira is also able to view business sales records more easily because sales records such as profit, capital and other costs will be displayed automatically in this system. In terms of specially developed applications, Shawllira customers can enjoy faster access in viewing the various types of products sold as well as the total stock of products available at the time and subsequently can make purchases through this application. To ensure the smooth running of online buying and selling activities, only registered users are allowed to access this application and customers can register to use this application. Through this system, administrators can access business data and sales data more accurately and customers can also enjoy the convenience of purchasing Shawllira products in the application more quickly and easily. The development of these web applications and systems can help Shawllira and its customers to enjoy a more organized and convenient facility while being able to store data more securely and systematically.